Formation of hydrophobic surface using two stages electrodeposition method - Ani, Mohd Hanafi; Ramli, Nor Shahirah; Wan Yusoff, Wan Ahmad Yusmawiza; Mustafah, Yasir Mohd.; Othman, Raihan (Trans Tech Publications, Switzerland, 2015)
A simple and economical route based on a ZnCl2 mediated process was developed to synthesize hierarchical flower-like ZnO micro/nanoflakes on the surface of copper foil by 2 stages electrodeposition method (2M ZnCl2 – 0.5M ZnCl2). The prepared flakes were characterized by XRD and SEM. The morphology of ZnO can be tuned from simple isolated nanoflakes to ordered flower-like shape using this method. The surfaces retain good hydrophobic stability in long period time.